2021
DOI: 10.1007/s10096-021-04323-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of public health measures on the post-COVID-19 respiratory syncytial virus epidemics in France

Abstract: Since the beginning of the COVID-19 pandemic, other respiratory illnesses decreased worldwide. This study described the consequences of public health measures on respiratory syncytial virus (RSV) severe infections in France, where an interseasonal resurgence of RSV occurred recently. All patients admitted to Necker Hospital (Paris) between August 2018 and April 2021 with a diagnosis of RSV-associated acute lung respiratory infection (ALRI) were enrolled. Characteristics of subjects with RSV-associated ALRI in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
104
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(125 citation statements)
references
References 18 publications
16
104
3
2
Order By: Relevance
“…Previous studies have revealed a major impact of COVID-19 pandemic mitigation measures on transmissible diseases, such as, in the paediatric population, gastroenteritis, common cold, bronchiolitis and acute otitis media, but also measles [7,14]. However, a resurgence of some other common airborne infectious diseases has been observed in the setting of relaxed physical distancing recommendations, such as the delayed inter-seasonal respiratory syncytial virus (RSV) epidemic in France and in other parts of the world [15][16][17]. For now (December 2021), we have not observed a pertussis resurgence despite the end of the first lockdown and school fully reopening in France.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed a major impact of COVID-19 pandemic mitigation measures on transmissible diseases, such as, in the paediatric population, gastroenteritis, common cold, bronchiolitis and acute otitis media, but also measles [7,14]. However, a resurgence of some other common airborne infectious diseases has been observed in the setting of relaxed physical distancing recommendations, such as the delayed inter-seasonal respiratory syncytial virus (RSV) epidemic in France and in other parts of the world [15][16][17]. For now (December 2021), we have not observed a pertussis resurgence despite the end of the first lockdown and school fully reopening in France.…”
Section: Discussionmentioning
confidence: 99%
“…recently reported that, at the beginning of the COVID-19 pandemic, the usual winter 2020/2021 Respiratory Syncytial Virus (RSV) peak did not occur in Oxfordshire, UK, with an inter-seasonal rise several months later, 1 as described worldwide. 2 , 3 , 4 , 5 , 6 We previously described, in our French tertiary hospital, that the delayed RSV 2020/2021 outbreak involved less adults and was associated with more hospitalization, higher age of pediatric inpatients and milder median clinical phenotype than observed before the COVID-19 pandemic. 2 In France, severe public restrictions (national lockdown, curfew) ended in May-June 2021, but some measures have been maintained (universal masking policy in adults and children ≥6 years in healthcare settings, schools, public transportations and most indoor spaces, educational interventions for prevention of community and healthcare-associated respiratory infections).…”
mentioning
confidence: 91%
“… 2 , 3 , 4 , 5 , 6 We previously described, in our French tertiary hospital, that the delayed RSV 2020/2021 outbreak involved less adults and was associated with more hospitalization, higher age of pediatric inpatients and milder median clinical phenotype than observed before the COVID-19 pandemic. 2 In France, severe public restrictions (national lockdown, curfew) ended in May-June 2021, but some measures have been maintained (universal masking policy in adults and children ≥6 years in healthcare settings, schools, public transportations and most indoor spaces, educational interventions for prevention of community and healthcare-associated respiratory infections). Our study aims to evaluate (i) if these measures had an impact on the hospital burden of RSV in the 2021/2022 season when compared to the prepandemic outbreaks and (ii) if the epidemiological changes observed in 2020/2021 were also seen in 2021/2022.…”
mentioning
confidence: 91%
“…The COVID-19 pandemic changed the landscape of almost all other viral respiratory infections leading transiently to a major decrease of viral cases including a delayed RSV outbreak ( 10 ). Public health and restrictive measures targeted at controlling transmission of SARS-CoV-2 have altered the epidemiology and seasonality of many respiratory viruses ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%